Full lifecycle carbon emissions accounting and regional environmental impact assessment of typical open-pit coal mines - Mingqi LIU; Xiaoping ZHANG; Yu WANG; Zhipeng YANG; Xinhong YU; Agudamu HU; Guoqing YANG; Ying ZHU; Yingnan CAO; Wei LIU; Tianlong ZHENG; Yaoqiang HUO; et al. (Meitan xuebao, 2025)
Carbon emission accounting is an indispensable and important part of the synergistic goal of pollution reduction and carbon reduction, and the coal industry is one of the key areas of carbon emission reduction. In this study, a typical open-pit coal mine was taken as the research object, a carbon emission accounting model for the whole life cycle of coal products was constructed, the carbon emission inventory of each production link in the mining area was quantified, and the impact of carbon emissions in the open-pit mining area on the regional environment was evaluated. According to the life cycle assessment (LCA) methodology, the carbon emissions of coal mining enterprises can be categorized into phases including coal extraction, coal beneficiation, transportation and storage, utilization and consumption, as well as other associated processes. Within this model, sources of carbon emissions have been systematically summarized. Direct carbon emissions encompass CO2 emissions from fuel combustion and methane (CH4) fugitive emissions. Indirect carbon emissions, on the other hand, include those associated with the net purchase of electricity and water consumption. The results of the accounting process indicate that the annual carbon emission of open-pit coal mine is 1538178.60 tCO2e, and the carbon dioxide equivalent emission per 1 t of raw coal produced is 0.05 tCO2e, which mainly comes from methane fugitive emissions caused by coal mining and post-mine activities (accounting for 79.92%). In addition, carbon emissions from fossil fuel combustion account for 13.71% of the total carbon emissions; whereas emissions associated with electricity and water consumption represent the smallest proportion, at 6.37%. The average annual greenhouse gas emissions of open-pit coal mines in China in the past ten years are (3.24 ±0.77) ×107 tCO2e, which is equivalent to the annual carbon sequestration of (5.23 ±1.24) ×108 trees, which is converted into the annual carbon sequestration of (113.83 ±27.00) hectares of poplar forests. At the same time, according to the current mining methods and processes, the country will generate more than 2.3 billion yuan of additional economic expenditure every year, and with the increase in open-pit coal mining, it will increase year by year. Therefore, reducing carbon emissions during the open-pit coal mining process is of significant importance, with particular emphasis needed on mitigating fugitive emissions. The research findings have significant implications for the development of a standardized carbon emissions accounting system in the coal industry and for assessing its regional environmental impact.